2021
DOI: 10.1111/evo.14174
|View full text |Cite
|
Sign up to set email alerts
|

Wing plasticity and associated gene expression varies across the pea aphid biotype complex

Abstract: Developmental phenotypic plasticity is a widespread phenomenon that allows organisms to produce different adult phenotypes in response to different environments. Investigating the molecular mechanisms underlying plasticity has the potential to reveal the precise changes that lead to the evolution of plasticity as a phenotype. Here, we study wing plasticity in multiple host‐plant adapted populations of pea aphids as a model for understanding adaptation to different environments within a single species. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Most challenges to Dollo's law come from macroevolutionary approaches and include a large number of examples, such as shell coiling in limpets (Collin and Cipriani 2003), compound eyes in ostracods (Syme and Oakley 2012), sex and parasitism in mites (Klimov and O'Connor 2013;Domes et al 2007), mandibular teeth in frogs (Wiens 2011), limb evolution (Kohlsdorf and Wagner 2006), eggshells and oviparity (Lynch and Wagner 2010;Recknagel et al 2018;Esquerré et al 2020) in Squamata. At the same time, several possible mechansisms underlying the reversible evolution of complex traits, have been proposed, including phenotypic plasticity (Visser et al 2021;Parker et al 2021) and reticulate evolution (Horreo et al 2020). Examples of compensatory mutations which have been able to rescue the once-lost functionality of genes have also been found (Esfeld et al 2018) and it has been observed that a reversal to a lost ancestral state could happen through changes in relatively few genes (Seher et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most challenges to Dollo's law come from macroevolutionary approaches and include a large number of examples, such as shell coiling in limpets (Collin and Cipriani 2003), compound eyes in ostracods (Syme and Oakley 2012), sex and parasitism in mites (Klimov and O'Connor 2013;Domes et al 2007), mandibular teeth in frogs (Wiens 2011), limb evolution (Kohlsdorf and Wagner 2006), eggshells and oviparity (Lynch and Wagner 2010;Recknagel et al 2018;Esquerré et al 2020) in Squamata. At the same time, several possible mechansisms underlying the reversible evolution of complex traits, have been proposed, including phenotypic plasticity (Visser et al 2021;Parker et al 2021) and reticulate evolution (Horreo et al 2020). Examples of compensatory mutations which have been able to rescue the once-lost functionality of genes have also been found (Esfeld et al 2018) and it has been observed that a reversal to a lost ancestral state could happen through changes in relatively few genes (Seher et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, activation of TOR activity in honeybees is responsible for the developmental transition from facultatively sterile workers to reproductive queens, while repressing TOR activity could induce worker characters in queen-destined individuals ( Michalak et al, 2007 ). Transcriptomic analysis in maternal crowding of pea aphids suggested that genes functionally related to TOR signaling pathway were differentially expressed in mother aphids ( Parker et al, 2021 ). We therefore hypothesized that the canonical pathway of TOR-REPTOR-autophagy may be responsible for developmental plasticity of the wing disc in aphids, in accordance with lower TOR abundance in wingless-destined morph.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, activation of TOR activity in honeybees is responsible for the developmental transition from facultatively sterile workers to reproductive queens, while repressing TOR activity could induce worker characters in queen-destined individuals ( Michalak et al, 2007 ). Transcriptomic analysis in maternal crowding of pea aphids suggested that genes functionally related to TOR signaling pathway were differentially expressed in mother aphids ( Parker et al, 2021 ). We therefore hypothesized that the canonical pathway of TOR-REPTOR-autophagy may be responsible for developmental plasticity of the wing disc in aphids, in accordance with lower TOR abundance in wingless-destined morph.…”
Section: Discussionmentioning
confidence: 99%